Correlation between Carbapenem Consumption and Carbapenems Susceptibility Profiles of Acinetobacter baumannii and Pseudomonas aeruginosa in an Academic Medical Center in Thailand - Taniya Paiboonvong (2022)
The emergent issue of carbapenem-resistant Acinetobacter baumannii (A. baumannii) and Pseudomonas aeruginosa (P. aeruginosa) is a major problem in Thailand. The wide use of carbapenems can increase selective pressure of bacterial resistance. The objective of this study was to determine the relationship between carbapenem consumption and the susceptibility rates of A. baumannii and P. aeruginosa, including multi-drug resistance (MDR) strains. This was a retrospective study. Carbapenem consumption and susceptibility profiles were collected from 2007 to 2013 at the Her Royal Highness Princess Maha Chakri Sirindhorn Medical Center, Thailand. We found that the susceptibility rate of A. baumannii to imipenem and meropenem from the sputum and the bronchoalveolar lavage (BAL) specimens was significantly decreased during the study period, but no significant change was found in the P. aeruginosa data. The relationship between carbapenem consumption and the susceptibility rate of A. baumannii had a clear association with the use of ertapenem. We found a statistically significant negative correlation between ertapenem consumption and the susceptibility rate of A. baumannii to imipenem (r = −0.91; p = 0.004) and meropenem (r = −0.97; p = 0.000) in the data from the non-ICU wards. In addition, imipenem use had a moderate negative correlation with the MDR P. aeruginosa data but no statistical significance (r = −0.714; p > 0.05). In conclusion, our study suggested there is an association between carbapenem use and the susceptibility of A. baumannii and P. aeruginosa. Notwithstanding this, information on ecological factors should be considered for further study. These findings showed the need to optimize the carbapenem prescription policy. Avoiding carbapenem overuse and rethinking the appropriate initial therapy might decrease the rate of resistant organisms.